1998
DOI: 10.2307/1542510
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salinity on Sperm Motility, Fertilization, and Development in the Pacific Herring, Clupea pallasi

Abstract: We investigated the effects of salinity on fertilization and early development in a population of Pacific herring, Clupea pallasi, that migrate from oceanic waters into the San Francisco Bay estuary to spawn. The salinity range for fertilization fell between 8 and 28 ppt, with an optimal range of about 12 to 24 ppt. In comparison, the range for a population of C. harengus membras (Airisto Sound, Finland) that reside year-round in the Baltic Sea was 4 to 24 ppt. Roles for both Na+ and K+ were indicated in C. pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
38
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 17 publications
4
38
0
Order By: Relevance
“…Sperm motility was assessed with either a 10ϫ or 20ϫ objective lens by using the following qualitative index: 0 ϭ no motility, 1ϩ ϭ Ͻ25% motility, 2ϩ ϭ 25-50% motility, 3ϩ ϭ 50-75% motility, 4ϩ ϭ Ͼ75% motility (13,14,16 (23). In some experiments, the Ca 2ϩ channel blockers nifedipine (100 M) or flunarizine (10 M) or the Na ϩ ͞Ca 2ϩ exchange inhibitors bepridil (50 M), dichlorobenzamil (10 M), or KB-R7943 (10 M) were preincubated (5 min) with sperm before Ca 2ϩ i measurements.…”
Section: Isolation Of Smifmentioning
confidence: 99%
See 4 more Smart Citations
“…Sperm motility was assessed with either a 10ϫ or 20ϫ objective lens by using the following qualitative index: 0 ϭ no motility, 1ϩ ϭ Ͻ25% motility, 2ϩ ϭ 25-50% motility, 3ϩ ϭ 50-75% motility, 4ϩ ϭ Ͼ75% motility (13,14,16 (23). In some experiments, the Ca 2ϩ channel blockers nifedipine (100 M) or flunarizine (10 M) or the Na ϩ ͞Ca 2ϩ exchange inhibitors bepridil (50 M), dichlorobenzamil (10 M), or KB-R7943 (10 M) were preincubated (5 min) with sperm before Ca 2ϩ i measurements.…”
Section: Isolation Of Smifmentioning
confidence: 99%
“…This range of salinities correlates with the optimal salinity regime for fertilization and early development in Pacific herring (14). Previous studies have shown that extracellular Na ϩ ([Na ϩ ] o ) and extracellular Ca 2ϩ ([Ca 2ϩ ] o ) influence both sperm motility and fertilization (11)(12)(13)(14)18). Sperm motility can be initiated in the absence of SMIF by low-Na ϩ (2 mM) seawater (NaF; ref.…”
mentioning
confidence: 95%
See 3 more Smart Citations